Role of Physical Medicine and Rehabilitation in Phantom Pain Management - Yudith Dian Prawitri; Ratna Darjanti Haryadi (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Limb amputation often results in the alteration of painful (phantom and stump pain) and nonpainful sensoryexperiences (phantom sensation). It is important to know the characteristics of sensory experiences to avoidmistakes in identifying phantom pain. Phantom pain can cause disability for patient, disturbance in mobility,and deteriorate the quality of post-amputated patient. Management of phantom pain include pharmacologytreatment, surgery, anasthesia also psychotherapy. Physical medicine and rehabilitation program such asphysical therapy, biofeedback, desensitization, occupational therapy, mirror therapy, and applying prosthesisshould be performed not only to manage the pain, but also to improve functional level to increase patient’squality of life.Key Words: Amputation; Phantom limb pain; Stump pain; Sensation; Rehabilitation.